2016
DOI: 10.3892/ol.2016.5360
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of breast cancer prognosis among young and older women in a Brazilian cohort of 738 patients, 1985–2002

Abstract: Invasive breast cancer (BC) is infrequent among women aged ≤40 years, however, the disease outlook in these younger patients is generally worse than among older women. The present study aimed to compare socio-demographic, clinical and pathological characteristics, and their association with long-term survival, between two random cohorts of young (≤40 years) and older (50–69 years) Brazilian patients with BC. The cohort comprised of 738 randomly selected women who were diagnosed with BC at Barretos Cancer Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 41 publications
4
18
0
1
Order By: Relevance
“…It does appear that conflicting results regarding the role of tumor biology, including tumor grade, ER, PR, and HER2 status in young breast cancer. Several prior studies showed similar or inferior outcomes related to ER positive status in young patients [21][22][23][24][25][26][27], while others demonstrated superior outcomes associated with ER positive status [28,29]. It was hypothesized that young patients have lower compliance with hormonal therapy [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It does appear that conflicting results regarding the role of tumor biology, including tumor grade, ER, PR, and HER2 status in young breast cancer. Several prior studies showed similar or inferior outcomes related to ER positive status in young patients [21][22][23][24][25][26][27], while others demonstrated superior outcomes associated with ER positive status [28,29]. It was hypothesized that young patients have lower compliance with hormonal therapy [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, patients who were untreated with systemic therapy also showed inferior survival outcomes in young luminal-B patients [14]. In addition, the prognostic effect of HER2 status on survival outcomes had an impact on the receipt of the anti-HER2 therapy [29][30][31][32][33]. A study from Japan showed that the triple-negative breast cancer had the worst outcomes in patients aged ≤40 years, while comparable outcomes were found among the luminal A, luminal B, and HER2 overexpression subtypes [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study from Chile that compared survival rates at 5 years between patients ≤40 and ≥70 years old, with stage I to III disease, it was concluded that young patients had a higher recurrence rate than older women (25.8% versus 11.7%) but had lower mortality (17.3% versus 29.4%), potentially due to lower chemotherapy use in the elderly population with high-risk tumours [16]. Similarly, in a historical cohort of women with BC, diagnosed between 2000 and 2002 in Brazil, age < 30 years was significantly associated with increased risk of death (hazard ratio (HR) = 3.09; 95% confidence interval (CI): 1.25−7.67) [17]. Another Mexican study revealed that young patients had poorer disease-free survival (DFS) and overall survival (OS) compared to those > 40 years (75.6% versus 85.7%, p < 0.001 and 78.6% versus 83.4%, p = 0.012, respectively) [18].…”
Section: Being Young As a Factor For Worse Prognosis In Latin Americamentioning
confidence: 99%
“…Un estudio en EEUU muestra que las mujeres <36 años tienen mayor probabilidad de tener EC II o III al momento del diagnóstico comparado con mujeres mayores (60% contra 43%; p<0,001)(6). De igual manera, en Brasil se reportó una asociación entre ser joven (<40 años) y presentarse en mayor proporción con EC II y III(39).En Perú esta tendencia podría estar acentuada, debido a la dificultad en acceso a los servicios de salud, y la baja sobrevida que encontramos en estadíos avanzados (solo 19% a los 5 años en EC IV).El subtipo triple negativo se asoció a un 81% de aumento en el riesgo de muerte, mientras que no hubo diferencias entre los otros subtipos. Esto difiere con nuestro hallazgo previo en SLE.…”
unclassified